2003
DOI: 10.1002/adma.200305400
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Control of Tapered and Multi‐Junctioned Carbon Tubular Structures

Abstract: Thin walled, carbon tubular structures (see Figure and also cover) with varying inner diameters in the form of nozzles, straight tubes, tube‐on‐cones, and funnels have been synthesized by in‐situ control of gallium‐carbon wetting behavior using gas phase chemistry. In addition, carbon tubular structures with large internal diameters have been coalesced during growth to create Y‐junctions suitable for micro/nano‐fluidic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…The CMT synthesis procedure and the structure have been described in detail elsewhere. [28][29][30] Although the present technique of using trimethyl gallium is expensive, this process presents a route of using Ga as a catalyst in the presence of methyl radical species for the inexpensive large-area synthesis of CMTs. The SEM image in Figure 1a shows a large area of the as-synthesized CMTs that are several micrometers in length.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CMT synthesis procedure and the structure have been described in detail elsewhere. [28][29][30] Although the present technique of using trimethyl gallium is expensive, this process presents a route of using Ga as a catalyst in the presence of methyl radical species for the inexpensive large-area synthesis of CMTs. The SEM image in Figure 1a shows a large area of the as-synthesized CMTs that are several micrometers in length.…”
Section: Resultsmentioning
confidence: 99%
“…27 Later, thin-walled CMT synthesis with control over the conical angles and microtube diameters was demonstrated. 28,29 Another study showed that these CMTs can be synthesized during thermal decomposition of a Ga precursor. 30 Recently, Sn particles encapsulated in porous multichannel carbon microtubes have shown a capacity retention of ∼650 mAh g -1 after 140 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the growth mechanism described in Figure 5, the conical angle of the evolving morphology can be related to the contact angle between gallium and the carbon wall by the following relationship. In our synthesis method, 13,14 we change the contact angle, , by varying the gas phase chemistry, allowing us to successfully control the conical angles of the carbon tubular structures. Under CH 4 /H 2 gas phase chemistries gallium does not wet carbon readily due to its high surface energy.…”
Section: (B) Carbon Microtubesmentioning
confidence: 99%
“…Recently, we reported a synthesis technique to synthesize carbon tubular structures with larger inner diameters, tunable morphologies and with no internal obstructions so as to enable micro/nanofluidic applications. 13,14 In this paper, we present the synthesis and applications of two new forms of graphite at the nanoscale: carbon nanopipettes and carbon microtubes with controllable morphologies. The synthesis methods and the corresponding growth mechanisms involved for both types of structures will be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…These properties make gallium an important element for chemical vapor synthesis of nanomaterials [18].…”
Section: General Background On Galliummentioning
confidence: 99%